Frontispiece: Investigating Ugi/Passerini Multicomponent Reactions for the Site‐Selective Conjugation of Native Trastuzumab. Issue 61 (4th November 2020) - Sornay, Charlotte; Hessmann, Steve; Erb, Stéphane; Dovgan, Igor; Ehkirch, Anthony; Botzanowski, Thomas; Cianférani, Sarah; Wagner, Alain; Chaubet, Guilhem
Abstract : Gemini reactions : In their Full Paper on page 13797 ff., G. Chaubet et al. have investigated the potential of Ugi and Passerini multicomponent reactions for the site‐selective conjugation of native trastuzumab. The conjugation proved to tolerate various aldehyde and isocyanide, and a plug‐and‐play approach was devised, allowing the facile generation of doubly labelled conjugates and antibody–drug conjugates.